Coincidence of Incomplete Pentalogy of Cantrell and Meningomyelocele in a Dizygotic Twin Pregnancy - Hakan Timur; Aytekin Tokmak; Hatice Bayram; Esra Şükran Çakar; Nuri Danışman (Hindawi Limited, 2015)
Pentalogy of Cantrell is an extremely rare and lethal syndrome. Ectopia cordis is frequently found in fetuses with POC but not required for incomplete forms. Likewise, meningomyelocele is a relatively uncommon neural tube defect affecting central nervous system and associated with neurological problems. Herein, we presented a woman with dizygotic twin pregnancy having coincidence of incomplete POC and MMC in each individual fetus, which has never been reported previously.